This was the first steam fire engine, located in Salem, and pulled by horses. The firemen are standing in front of the engine. - (:unkn) unknown (Forsyth County Public Library, 2010)
Photo made in the 1890s.
This was the first steam fire engine, located in Salem, and pulled by horses. The firemen are standing in front of the engine, at the station.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth